2019
DOI: 10.1055/a-1032-3346
|View full text |Cite
|
Sign up to set email alerts
|

Laccaridione C, a Bioactive Polyketide from the Fungus Montagnula sp.

Abstract: The new polyketide laccaridione C (1) was obtained by bioassay-guided isolation of organic extracts of the fungal strain CF-223743, isolated from dung collected in a forest of Grand Comoros Island. Its structure was established using spectroscopic methods, namely HRMS and 1D and 2D NMR. The new compound was tested against seven cancer cell lines, evidencing effective activity against melanoma (A2058) with an IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Alternaria destruens is a beneficial soil microbe that can promote the growth of plants 82 ; this fungus then, can be further investigated for its benefits of vegetative growth in heavily contaminated soil as in Marac. Apart from the few studies that include Montagnula scabiosae in taxonomic and phylogenetic studies 83 – 85 , this species together with Montagnula opulenta are not reported in the literature for any impactful research use until now.…”
Section: Discussionmentioning
confidence: 99%
“…Alternaria destruens is a beneficial soil microbe that can promote the growth of plants 82 ; this fungus then, can be further investigated for its benefits of vegetative growth in heavily contaminated soil as in Marac. Apart from the few studies that include Montagnula scabiosae in taxonomic and phylogenetic studies 83 – 85 , this species together with Montagnula opulenta are not reported in the literature for any impactful research use until now.…”
Section: Discussionmentioning
confidence: 99%